Aplikasi Berbagai Jenis Pupuk terhadap Serangga Terrestrial dan Pertumbuhan Tanaman Padi Hitam - Vira Kusuma Dewi; Reynaldi Reynaldi; Toto Sunarto; Santika Sari; Lindung Tri Puspasari; Rika Meliansyah (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
Paddy field ecosystem is a complex ecosystem and build a food web. Tri-trophic interaction in paddy field involves rice plants as producers, phytophagous and neutral insects as first consumers, and their natural enemies as second consumers..This study was conducted to analyze the effect of siam weed and neem cake compost on abundance arthropod in black rice. The experiment was carried out in paddy field at Jatinangor from May to November 2018. The experimental method was used a randomized Complete Block Design with five treatment as follow neem cake, siam weed compost, cow manure, synthetic fertilizer and control) and six replications. The results showed, that arthropods abundance and plant performance including plant height, tiller number and SPAD value were higher in siam weed compost and neem cake treatment if compared with other treatments. Furthermore, there were strong correlation between insect herbivore with natural enemies in siam weed treatment.